PENGETAHUAN BIDAN MERUPAKAN FAKTOR DOMINAN TERHADAP KEPATUHAN BIDAN MENERAPKAN ASUHAN PERSALINAN NORMAL - Fauziah Fauziah; Jujum Rumdasih; Erna Mesra (Poltekkes Kemenkes Jakarta III, 2014)
Midwives are health care worker that has duty in maternity room. Normal Delivery Care (NDC) Training is training of clean and safe delivery assistance by considering five aspects, which is making clinical decision, loving mother, infant care, infection prevention, referral, documentation. District Health Center in East Jakarta handling normal labor annually as much 1.155 (85%), midwives as much 44 people, 90% has attended NDC Training, has applied it. This research knows the relation between training, knowledge, attitude, work duration with NDC application, dominant factor in NDC application, carried out in maternity room in East Jakarta. Sample is all midwives that worked in maternity room which is 40 midwives. The design of research is Cross Sectional. The result shows, midwives that obey the NDC application is 70%, who doesn't is 30%, there is a relation between training, knowledge, attitude with NDC application, duration of work doesn't. Knowledge is the most dominant factor to NDC application, P value is 0.014, OR value 24.978, knowledgable midwives is more obed 24 times than aknowledgable midwives, considering that the knowledge is the most dominant, Health Department, Indonesian midwives assosiation should increase knowledge skill of midwives so qualified human resources can increase too.